Title News Framing of the 12 Percent VAT Increase in Online Media : (Pan and Kosicki’s Framing Analysis on Antara News and Kompas.com for the Period of December 2024 – January 2025) - Robbibatus Saaidah; Titin Setiawati; Sri Mustika (Badan Penerbit STIEPARI Press, 2025)
This study aims to analyze how the news framing of the Value Added Tax (VAT) increase to 12 percent is constructed by two online media platforms, namely Kompas.com and Antara News, from December 2024 to January 2025. The method used is a framing analysis model by Pan and Kosicki with a descriptive qualitative approach. The data were obtained through purposive sampling by selecting 10 popular news articles from each media outlet. The results of the study show that both media present different framing tendencies: Kompas.com emphasizes public and business responses, while Antara News focuses more on the government’s perspective. The differences are evident in the syntactic, script, thematic, and rhetorical structures of each media outlet. These findings indicate that the construction of reality is influenced by editorial interests and audience segmentation.